Testing Long-Run Neutrality of Money in Thirteen Asian Developing Countries - Puah, Chin Hong (2001)
The long-run neutrality (LRN) proposition suggests that a permanent change in the money stock has no long-run consequences on the level of real output. Most of the empirical studies of the neutrality of money are focused on industrialised countries. The main objective of this study is to investigate the LRN of money on real output in thirteen Asian developing economies using a reduced-form ARIMA model developed by Fisher and Seater (1993). This study makes use of annual data for money supply (Ml and M2) and real GDP, which spans from 1950 to 1997. Consideration of two measures of money supply serves as a sensitivity analysis for the potential effects of different measures of money on real output. In this study, the sample countries include: Bangladesh, India, Indonesia, Malaysia, Myanmar, Nepal, Pakistan, Philippines, Singapore, South Korea, Sri Lanka, Taiwan, and Thailand.This study uses cross-sectional data from the thirteen Asian countries to examine one of the monetary propositions, that is, changes in the money supply are not associated with the permanent changes in real output. Money (both Ml and M2) is said to have no influence on the movements of real output in the long run. For time series data, results of the unit root test suggest that LRN is testable in twelve of the thirteen countries and money is found to be neutral in nine of the twelve countries. This conclusion is robust whether Ml or M2 is used as the money measure. However, in three countries (Indonesia, South Korea and Taiwan), the LRN test outcomes are sensitive to the measure of money used. Only in India, both Ml and M2 are not long run neutral with respect to real output. Based on these results, LRN can be said to describe a general feature of the Asian developing economy. This indicates that money supply do not play an important role in influencing the long run real output movement. Therefore, both monetary aggregates probably are not useful policy instrument in the Asian countries. However, the narrow money supply might be treated as a useful policy instrument in some of the countries since it has the ability to influence the long-run movement of real output in these countries.